Experimental Study of the Bone Marrow Aspirate Injection Effect into Denervated Muscle (Clinical Manifestations of Limb Denervation) - Strafun, S.S.; Lysak, A.S.; Huzovatyi, O.Yu. (TERRA ORTHOPAEDICA, 2022)
Relevance. Peripheral nerve injuries are potentially disabling lesions, which account for about 2-3% of all injuries. In order to study the clinical manifestations of limb denervation in the early and late stages, we conducted an experimental study.Objective: in the experiment, to study the effect of bone marrow aspirate injection into the target muscles on denervation-reinnervation processes by studying the clinical manifestations of denervation (presence of trophic ulcers, edema, or muscle wasting).Materials and Methods. The experiment was performed on 36 rabbits, which were divided into four groups: a group of pseudo-operated animals, group 1 (neurotomy and sciatic nerve suture), group 2 (on-time injection of bone marrow aspirate), and group 3 (delayed injection of bone marrow aspirate). Detection of hypotrophy or edema of the tibia was performed by determining the percentage of leg circumference of the operated on and intact limbs. Clinical manifestations of limb denervation were recorded during the examination of experimental animals before their euthanasia.Results. When comparing the number of complications in group 1 and group 2, more complications of the denervation process was observed in group 1. At the same time, no difference was found between group 1 and group 3, as well as between group 2 and group 3. When comparing the indicators of hypotrophy, the difference between group 1 and group 2, as well as a significant difference (p<0.05) between group 1 and group 3, with a predominance of hypotrophy in group 2 and group 3 were revealed.Conclusions. The injection of bone marrow aspirate into the target muscles during surgery and in the early stages of reinnervation helped to reduce the clinical manifestations of the denervation process. Delayed administration of bone marrow aspirate to target muscles significantly (p<0.05) helped to reduce edema of denervated target muscles.